Interactive effects of ocean acidification and temperature on oxygen uptake rates in Calanus hyperboreus nauplii - Espinel-Velasco, Nadjejda; Gawinski, Christine; Kohlbach, Doreen; Pitusi, Vanessa; Graeve, Martin; Hop, Haakon (Frontiers in Marine Science, 2023)
The Arctic region is undergoing rapid and significant changes, characterized by high rates of acidification and warming. These transformations prompt critical questions about the resilience of marine communities in the face of environmental change. In the Arctic, marine zooplankton and in particular calanoid copepods play a vital role in the food web. Changes in environmental conditions could disrupt zooplankton communities, posing detrimental consequences for the entire ecosystem. Copepod early-life stages have been shown to be particularly sensitive to environmental stressors since they represent a bottleneck in the life cycle. Here, we investigated the responses of 4-day old Calanus hyperboreus nauplii when exposed to acidification (pH 7.5 and 8.1) and warming (0 and 3°C), both independently and in combination. Naupliar respiration rates increased when exposed to a combination of acidification and warming, but not when exposed to the stressors individually. Moreover, we found no discernible differences in lipid content and fatty acid (FA) composition of the nauplii across the different experimental treatments. Wax esters accounted for approximately 75% of the lipid reserves, and high amounts of long chain fatty acids 20:1 and 22:1, crucial for the reproduction cycle in copepods, were also detected. Our results indicate a sensitivity of these nauplii to a combination of acidification and warming, but not to the individual stressors, aligning with a growing body of evidence from related studies. This study sheds light on the potential implications of global change for Arctic copepod populations by elucidating the responses of early-life stages to these environmental stressors.